1985
DOI: 10.1152/jn.1985.54.2.348
|View full text |Cite
|
Sign up to set email alerts
|

The role of cerebral cortex in the generation of voluntary saccades: a positron emission tomographic study

Abstract: The purpose of this study was to define the location and behavior of cerebral structures within the normal human brain that participate in the generation of voluntary saccadic eye movements. Changes in regional cerebral blood flow (rCBF) during task performance were assumed to reflect like changes in regional neuronal activity induced by the task. The locations of all rCBF changes were described in stereotaxic coordinates. Cerebral blood flow (CBF) was measured with positron emission tomography (PET) and bolus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(124 citation statements)
references
References 0 publications
14
107
3
Order By: Relevance
“…We did not observe any signiWcant activation in the SEF during saccadic eye movements. Activation in the SEF related to reXexive or voluntary saccade eye movements has been reported by some (Fox et al 1985;Darby et al 1996;Petit et al 1996;Law et al 1998;Luna et al 1998;Muri et al 1998;Berman et al 1999;Nobre et al 2000), but not by others (Anderson et al 1994;Mort et al 2003).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We did not observe any signiWcant activation in the SEF during saccadic eye movements. Activation in the SEF related to reXexive or voluntary saccade eye movements has been reported by some (Fox et al 1985;Darby et al 1996;Petit et al 1996;Law et al 1998;Luna et al 1998;Muri et al 1998;Berman et al 1999;Nobre et al 2000), but not by others (Anderson et al 1994;Mort et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we also found that reXexive saccades yielded activation in the FEF, PEF, MT/V5 and in the angular gyrus, as well as in the cerebellum, more speciWcally in the cerebellar lobule VI, crus I and in the vermis VI and VII. For voluntary saccades, PET studies have shown activation in FEF (Fox et al 1985;Petit et al 1996;Law et al 1998), SEF (Fox et al 1985;Petit et al 1996;Law et al 1998), PEF (Petit et al 1996), PVA/V1 (Fox et al 1985), the anterior cingulate cortex (Paus et al 1993), the precuneus (Petit et al 1996), the midbrain and the cerebellar vermis (Petit et al 1996;Law et al 1998). fMRI studies have also shown activation in FEF (Darby et al 1996;Corbetta et al 1998), SEF (Darby et al 1996), PEF, PVA/V1, and the posterior vermis of the cerebellum (Corbetta et al 1998), as well as in V4.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in absolute blood flow in areas typically affected by cognitive tasks are rarely Ͼ5-10% of the brain's resting blood flow. These modest modulations in ongoing circulatory activity often do not appreciably affect overall brain blood flows during even vigorous sensory and motor activity (45)(46)(47). For interesting exceptions related to more demanding cognitive tasks see refs.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well known that the SMA, in addition to the MI, are active in such types of movements that does not require temporal or spatial control in any complex manner. Changes in rCBF have been reported during simple limb movements [9,17,18,21]. Movement related potentials have also been recorded in the SMA before flexion or extension of hand or arm joints [5,27,30,74].…”
Section: Neurons In Both Sma and MI Are Active In Relation To Relativmentioning
confidence: 97%